A note on the role of monetary policy when natural gas supply is inelastic - Alfons J. Weichenrieder (Leibniz Institute for Financial Research SAFE, 2022)
This note argues that in a situation of an inelastic natural gas supply a restrictive monetary policy in the euro zone could reduce the energy bill and therefore has additional merits. A more hawkish monetary policy may be able to indirectly use monopsony power on the gas market. The welfare benefits of such a policy are diluted to the extent that some of the supply (approximately 10 percent) comes from within the euro zone, which may give rise to distributional concerns.
Keywords: E52; Q31; 330; energy crisis; monetary policy; natural gas